EFFECT OF FLEXURAL STRENGTH NON DENTAL GLASS FIBER REINFORCED COMPOSITE CONCENTRATION ON ARTIFICIAL SALIVA - Eko Hadianto; Muhammad Dian Firdausy; Budi Suhartono; Erdianto Setya Wardhana; Daffa Gemineo Dheona (Universitas Muhammadiyah Semarang, 2024)
Background : Composite resin is a commonly used material in dentistry due to its ease of application and aesthetic qualities. A specific type of this material, known as fiber reinforced composite, consists of a polymer matrix reinforced with fibers. This study aims to compare the impact of various concentrations of non-dental glass fibers on the flexural strength of composite resin when immersed in artificial saliva.Methodology : This study was experimental and followed a post-test only control group design. It included 18 specimens, each measuring 25x2x2 mm. The specimens were divided into three groups: the first group consisted of non-dental glass fiber reinforced composite with concentrations of 0%, 1%, and 2%. The data were analyzed using a One Way ANOVA parametric test.Results : The average flexural strength for the first group of non-dental glass fiber reinforced composite at 0% concentration was 52.496 MPa. For the second group, with a 1% concentration, it was 96.268 MPa. The third group, with a 2% concentration, had an average flexural strength of 134.791 MPa. The One Way ANOVA results yielded a p-value of 0.000Conclusion : The research results indicated that the highest flexural strength was observed in the non-dental glass fiber reinforced composite with a 2% concentration